PENGARUH KONFLIK KEPENTINGAN, MORALITAS INDIVIDU, DAN KOMPETENSI APARATUR TERHADAP PENCEGAHAN KECURANGAN DANA DESA - Niken; Narew, Ignasius; Manurun, Telysulvika; Gelatan, Longginus (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2026)
This research is motivated by the persistently high potential for fraud in village fund management, which can hinder the realization of accountable and transparent village governance. The purpose of this study is to analyze the influence of conflicts of interest, individual morality, and Village Official Competence on the prevention of village fund fraud. The research method used was a quantitative approach with an associative research design, utilizing primary data collected through questionnaires distributed to village officials involved in village financial management. The data were analyzed using structural equation modeling (SEM) to determine the relationship between the variables. The results indicate that conflicts of interest influence the prevention of village fund fraud, while individual morality and Village Official Competence do not. The conclusion of this study confirms that controlling conflicts of interest is a crucial factor in preventing village fund fraud, while improving individual morality and Village Official Competence still requires attention.